Pengaruh Independensi, Kompetensi dan Tanggung Jawab Pendeteksian Kecurangan Terhadap Pencegahan Kegagalan Audit - Dina Monalisa (Jurnal Pena-Mas Akuntansi, 2022)
Audit failures caused by accounting scandals in recent years were caused by not applying generally accepted auditing standards, including the lack of independence, competence, and responsibility of auditors in detecting audit failures. This study aims to determine how much influence the independence, competence, and responsibility of fraud detection have on the prevention of audit failure. The object of research includes independence, competence, and responsibility for fraud detection as independent or independent variables which are seen as having an effect on the dependent or dependent variable, namely the prevention of audit failure. This research method uses a descriptive research method with the type of relationship between the variables studied is a clause relationship. Variables were analyzed using descriptive statistics, path analysis, and SPSS 17 as a data processing tool. The data collected was obtained through the distribution of questionnaires, with auditors as respondents at KAP in Jakarta. The results show that the independence, competence, and responsibility for detecting fraud either simultaneously or partially have a significant effect on the prevention of audit failure.